Efektivitas Penggunaan Modal Kerja dalam Meningkatkan Laba Usaha PT Indofood Sukses Makmur Tbk pada Bursa Efek Indonesia - Zaira Hanla Diva; Santi Pertiwi Hari Sandi; Ery Rosmawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The purpose of this study is to determine the effectiveness of working capital utilization in increasing the profits of PT Indofood Sukses Makmur Tbk, a company listed on the Indonesia Stock Exchange. Secondary data was obtained from the company’s annual financial reports for the period 2020–2024. A quantitative descriptive method was employed. The analysis was conducted by measuring working capital turnover, cash turnover, and inventory turnover, as well as profitability ratios such as gross profit margin, net profit margin, return on investment, and return on equity, which were compared to industry standards. The research findings indicate that PT Indofood Sukses Makmur Tbk’s working capital management is effective in boosting the company’s profits, as evidenced by an inventory turnover ratio of 3.47 times—above the industry standard—as well as profitability ratios of 32.60% for gross profit margin (GPM), 10.37% for net profit margin (NPM), and 11.45% for return on equity (ROE). However, the company still needs to improve its working capital turnover, cash turnover, and ROI to optimize its financial performance. These findings demonstrate that the company’s use of working capital has been effective, as evidenced by the increase in net profit despite a temporary decline in 2020.